Mutation of Fnip1 is associated with B-cell deficiency, cardiomyopathy, and elevated AMPK activity - Siggs,OM; Stockenhuber,A; Deobagkar-Lele,M; Bull,KR; Crockford,TL; Kingston,BL; Crawford,G; Anzilotti,C; Steeples,V; Ghaffari,S; Czibik,G; Bellahcene,M; et al. (Proceedings of the National Academy of Sciences of the United States of America, 2016)
Folliculin (FLCN) is a tumor-suppressor protein mutated in the Birt–Hogg–Dubé (BHD) syndrome, which associates with two paralogous proteins, folliculin-interacting protein (FNIP)1 and FNIP2, forming a complex that interacts with the AMP-activated protein kinase (AMPK). Although it is clear that this complex influences AMPK and other metabolic regulators, reports of its effects have been inconsistent. To address this issue, we created a recessive loss-of-function variant of Fnip1. Homozygous FNIP1 deficiency resulted in profound B-cell deficiency, partially restored by overexpression of the antiapoptotic protein BCL2, whereas heterozygous deficiency caused a loss of marginal zone B cells. FNIP1-deficient mice developed cardiomyopathy characterized by left ventricular hypertrophy and glycogen accumulation, with close parallels to mice and humans bearing gain-of-function mutations in the γ2 subunit of AMPK. Concordantly, γ2-specific AMPK activity was elevated in neonatal FNIP1-deficient myocardium, whereas AMPK-dependent unc-51–like autophagy activating kinase 1 (ULK1) phosphorylation and autophagy were increased in FNIP1-deficient B-cell progenitors. These data support a role for FNIP1 as a negative regulator of AMPK.